d-Amino Acid Catabolism Is Common Among Soil-Dwelling Bacteria - Radkov, Atanas D (Microbes Environ, 2016)
Soil and rhizosphere environments were examined in order to determine the identity and relative abundance of bacteria that catabolize d- and l-amino acids as the sole source of carbon and nitrogen. All substrates were readily catabolized by bacteria from both environments, with most d-amino acids giving similar CFU counts to their l-amino acid counterparts. CFU count ratios between l- and d-amino acids typically ranged between 2 and 1. Isolates were phylogenetically typed in order to determine the identity of d-amino acid catabolizers. Actinobacteria, specifically the Arthrobacter genus, were abundant along with members of the α- and β-Proteobacteria classes.